The analysis of prognostic factors and treatment outcomes in breast cancer patients with brain metastasis - Benli Yavuz, Berrin; Kanyilmaz, Gul; Aktan , Meryem (Annals of Medical Research, 2022)
Aim: Breast cancer (BC) is among the most common causes of brain metastasis (BM). Brain metastasis leads to severe morbidity and mortality. Brain metastasis-related survival is not common despite all treatments. The aim of the present study is to compare the short-term or long-term surviving patients who underwent radiotherapy due to BM in our clinic regarding treatment modalities, and clinic-pathological characteristics as well as to investigate the factors that influence overall survival and progress for BM development. Materials and Methods: The data of 167 patients who were referred to radiotherapy due to BM were analyzed retrospectively. The patients were allocated to two groups: ones who survived less than, or more than, 14 months. The treatment, patient, and tumor characteristics were evaluated. Results: The frequencies of a better Karnofsky performance scores (p=0.001), her-2 positivity (p<0.001), the presence of a single BM (p=0.048), an absence of leptomeningeal disease (p=0.033), an absence of extracranial metastasis (p=0.033) and having received systemic therapy following BM (p<0.001) were higher in the group that survived longer. In the group that survived longer, having stage T1-2 disease and being under 40 years of age, and, in the group that survived less, receiving systemic therapy following BM development were found to be the factors effective on overall survival (OS). Conclusion: To the best of our knowledge, this is the first study to compare the prognostic features of breast cancer patients with BM who survived short-term or longer. In our single-center retrospective study, for the group that survived longer, having T1-2 stage disease and being under 40 were the independent predictive factors for OS in multi-variable analyses. Further studies are required to determine the groups that will have a longer change of survival and plan to receive more aggressive therapies.